A multi-country survey on access to healthcare and treatment services among individuals with critical medical care needs during the first wave of the pandemic - Morenike Oluwatoyin Folayan; Roberto Ariel Abeldaño Zuñiga; Jorma I. Virtanen; Oliver C. Ezechi; Muhammad Abrar Yousaf; Ala'a B. Al-Tammemi; Mohammed Jafer; Passent Ellakany; Eshrat Ara; Martin Amogre Ayanore; Anthonia Omotola Ishabiyi; Balgis Gaffar; et al. (BMC, 2023)
Abstract Background Healthcare services were significantly interrupted during the early phase of the COVID-19 pandemic. The aim of the present study was to determine the associations between sociodemographic factors and healthcare access during the first wave of the COVID-19 pandemic among individuals with critical care needs. Methods This was a secondary analysis of the data of 5,156 participants recruited from 152 countries during the first wave of the COVID-19 pandemic. The dependent variables were self-reported difficulty of access to health care, challenges with obtaining medication, and the use of alternative medical services. The independent variables were age at last birthday; sex at birth, level of education, employment status and the macro-social vulnerability status. The confounding variable was the country income level. Three multivariable logistic regression analyses were conducted to determine the associations between the dependent variables and the independent variables after adjusting for the confounder. Results Difficulty accessing health care services and obtaining medications was experienced by 1922 (37.3%) and 3746 (72.7%) participants respectively. Also, 1433 (27.8%) used alternative medical care. Retirees (AOR:1.59), unemployed (AOR:1.198), people living with HIV (AOR:2.36) and at increased risk of COVID-19 (AOR:2.10), people who used drugs (AOR:1.83) and transacted sex (AOR:1.971) had significantly higher odds for reporting difficulty with access to health care. Males (AOR:1.23), respondents with secondary level of education (AOR:1.39), retirees (AOR:2.19), unemployed (AOR:1.47), people living with HIV (AOR:2.46), people who used drugs (AOR:1.79), transacted sex (AOR:2.71) and those who might be (AOR: 1.66) and were at (AOR: 2.3) increased risk of severe COVID-19 had significantly higher odds for reporting difficulty with access to medications. People who used drugs (AOR:2.093) transacted sex (AOR:1.639), who might be (AOR: 1.211) and were at (AOR: 1.511) increased risk of severe COVID-19, and who had difficulty accessing usual healthcare (AOR: 9.047) and obtaining medications (AOR:2.16) had significantly higher odds of reporting alternative medical care use. People living with HIV (AOR:0.562) had significantly lower odds of using alternative medical care. Conclusion We identified populations who had challenges with access to healthcare and obtaining medications used alternative medical care except for people living with HIV. Priority attention should be given to alternative medical care use during future health pandemics.